Eco-ethology of shell-dwelling cichlids in Lake Tanganyika - Bills, Ian Roger (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1997)
Observations of habitats are reported. A series of underwater experiments were conducted in natural habitats to answer questions concerning a) why Lamprologus ocellatus and Lamprologus ornatipinnis bury gastropod shells refuges into the substrate, and b) to examine interspecies differences in shell-using behaviours. Some behaviour patterns were analysed using phylogenetic methods. Lamprologus ocellatus and L. ornatipinnis responded to new shells in a variety of ways, shells were moved, buried (and used) or hidden (buried and not used). How shells are utilised seems to be dependant on a complex of factors such as the size and quality of new the shell and the number already in the territory. Shell use may also be affected by neighbour species, sex, size and predation levels. There are interspecific differences in the size of shells used and the methods of shell use. The latter results in species-characteristic shell orientations, vertical burial in L. ocellatus and horizontal burial in L. ornatipinnis. Shell orientation does affect other species/use of shells. Shell movement and vertical orientation appear to be apomorphic while shell hiding and burial are pleisiomorphic within the genus Lamprologus. Numerous cues are involved in stimulating shell burial. Most of these cues are actively sought by the fish by external and internal inspections. Shell burial therefore appears to be a method of reducing the information gathering ability of potential shell-dwelling competitors. Shell burial can therefore be regarded as an investment process which enhances the residents ability to defend its territory. Males can also control the distribution of open shells within teritories and thus control mate access to shells. This behaviour could be a significant factor in the evolution of marked sexual dichromatism exhibited within the genus.
Keywords: Cichlids -- Africa, East; Cichlids -- Tanganyika, Lake; Fishes -- Behavior